The lost Gospel of Judas Iscariot : a new look at betrayer and betrayed - Ehrman, Bart D. (Oxford University Press, 2006)
The recent National Geographic special on the Gospel of Judas was a major media event, introducing to tens of millions of viewers one of the most important biblical discoveries of modern times. Now, a leading historian of the early church, Bart Ehrman, offers the first comprehensive account of the newly discovered Gospel of Judas, revealing what this legendary lost gospel contains and why it is so important for our understanding of Christianity. Ehrman, a featured commentator in the National Geographic special, describes how he first saw the Gospel of Judas--surprisingly, in a small room above.